(CSR) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2012 - 2014 - Siti Ramlah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This study aimed to analyze the influence of Corporate Social Responsibility disclosure of financial performance in the mining company listed on the Indonesia Stock Exchange. The mining company listed on the Indonesia Stock Exchange in 2012 as many as 34 companies. However, by using purposive sampling method then selected 10 companies that serve as the research sample. Financial performance as the dependent variable that is measured by Debt to Equity Ratio (DER) Return on Assets (ROA), and Earning per Share (EPS). With this type of associative research, seen the effect of CSR on DER, ROA  and EPS. Disclosure of Corporate Social Responsibility (CSR) is an independent variable, measured by the index of CSR in all aspects of CSR. Testing is done with descriptive statistics, classical assumption test and simple linear regression. The results of this study illustrate that the disclosure of Corporate Social Responsibility does not show positive and significant impact on Debt to Equity Ratio (DER), Return On Assets (ROA), and the but positive and significant effect on the Earning per Share (EPS), the mining company listed on the Stock Securities Indonesia Year 2012-2014.Keywords: DER, EPS,CSR disclosures, ROA.